Behavior and Sustainable Finance: A Bibliometric Approach - Elena Muñoz-Muñoz; Eva Crespo-Cebada; José C. Corchado; Carlos Diaz-Caro (Administrative Sciences, 2025)
This paper is intended to highlight the importance of developing knowledge on sustainable finance using bibliometric analysis. The study is based on a review of sources from two of the most prominent scientific databases in the world, Scopus and Web of Science (WOS). A total of 372 and 355 documents were obtained from Scopus and WOS, respectively. The data indicate an exponential increase in the number of publications over the years, suggesting a growing interest in the subject and a need for further research. The research groups appear to have little connection, and the studies are widely scattered both geographically and across different research areas. Sustainable finance is an increasingly interesting field of study, with numerous branches that require further research. One such branch is the analysis of green bonds and sustainable development.